Mallomonas lamii sp. nov. (Synurales, Chrysophyceae), a new species bearing large scales described from the tropics - Gusev, Evgeniy Sergeevich; Kulizin, Pavel; Guseva, Elena; Shkurina, Natalia; Kulikovskiy, Maxim (Phytotaxa, 2019)
A new species Mallomonas lamii sp. nov. is described from Vietnam based on silica-scale morphology studied by means of transmission and scanning electron microscopies. The species belongs to the Mallomonas matvienkoae complex and is characterized by large oval scales with a thick secondary layer with internal reticulation that covers the distal one-third of the scale. The scale morphology of Mallomonas lamii is very similar to that of the fossil taxon M. pleuriforamen. Scales of Mallomonas lamii were found at thirteen localities from six provinces in central and southern areas of Vietnam. The distributions and habitat conditions of the new species are summarized.